Characteristics of Stress and Experiences in the Relationship with Patients of Oncologists in Valledupar, Colombia - Ruiz-Lurduy, Rodrigo; Zubillaga Páez , Mayte; Blanco Pérez , Isadora; Muegues-Salas , Ángel Alexis (Psicooncología, 2025)
Introduction: This study addresses the stress of general practitioners and oncologists in a medium-sized city in Colombia. Its objectives were: 1) to describe the characteristics of stress among oncologists and 2) to analyze their experiences in the doctor-patient relationship.Method: An integrative design of methods was implemented. Data collection consisted of the Nowak Stress Profile to quantitatively measure stress and semi-structured interviews to delve deeper into the oncologists' experiences.Results: Physicians have psychological tools to maintain their mental health and that of their patients. The test results do not indicate significant or conclusive alarms; while the prescribed stress levels reflect exposure to stressful events, specialists diagnose them and take appropriate action. Protective emotional components, such as job satisfaction, are positively identified, while stressful components, such as bureaucratic procedures, impact their work and relationships with patients. Conclusion: Stress is a common symptom in oncology medical practice. Contrary to reports in the literature, this population does not experience extreme emotional crises. Risk factors are determined individually, indicating the need for ongoing monitoring and healthy mental health habits among these professionals.
Keywords: Oncologists; Life Experiences; Stress; Emotions; Cancer Care Facilities